Pengaruh Motivasi Ekstrinsik Terhadap Kinerja Pegawai Melalui Komitmen Organisasi dan Disiplin Kerja Sebagai Variabel Intervening (Studi Pada KPU Kabupaten dan Kota di Provinsi Banten) - Diah Novianti; Moh. Mukhsin; Hayati Nupus (GEMILANG: Jurnal Manajemen dan Strategi Bisnis, 2021)
This study aims to examine and analyze the effect of extrinsic motivation on employee performance through organizational commitment and work discipline. This research uses descriptive quantitative method with causality approach. The object of this research is the Regency and City KPU in Banten Province using a sample of 106 respondents. Questionnaire answers were measured using an interval scale of 1 – 10. Data were analyzed using the SmartPLS version 3.29 software. The results of this study stated that: 1). Extrinsic motivation has an effect on employee performance. 2). Extrinsic motivation has an effect on organizational commitment. 3). Extrinsic motivation affects work discipline. 4). Organizational commitment affects employee performance. 5). Work discipline affects employee performance. Organizational commitment and work discipline can mediate between extrinsic motivation in partial mediation.